Management of Indirect Hyperbilirubinemia; Comparison of Complications of Light Emitting Diode (LED) and Fluorescent Phototherapy - Sijjad Hussain, Muhammad Bilal Safdar, Sara Maqsood, Muhammad Naveed, Mujahid Razzaq, Mahwish Ejaz, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the frequency of complications (hyperthermia, skin eruption, dehydration) of LED phototherapy and fluorescent phototherapy in management of indirect hyperbilirubinemia in neonates Material and methods: This randomized control study was carried out from 1st June 2015 to 31 December 2016 at NNU of The Children`s Hospital Lahore using Non probability consecutive sampling technique after getting informed consent from parents. All basic demographic information of each variable (name, age) was noted and entered on Performa. SPSS-18 was used to interpret the data. Results: In our study the mean age was 1.98±0.83 days. Skin rash complication was observed in 43(13%) cases, dehydration was found in 48(14.5%) cases and hyperthermia was noted in 65(19.70%) patients. Practical Implication: Many setups in Pakistan are still using conventional fluorescent phototherapy machines. LED has lesser side effects as compared to conventional one so by using LED light source we can lessen the adverse effects of phototherapy that will be beneficial to the babies Conclusion: LED light source is effective for phototherapy with significantly lesser complication rate (hyperthermia, skin eruption, and dehydration) compared to fluorescent phototherapy in management of indirect hyperbilirubinemia in neonates. In this study LED phototherapy significantly showed fewer complications as compared to fluorescent phototherapy cases. Keywords: LED, Fluorescent, Hyperthermia, Skin, Rash, Dehydration, Neonates, Hyperbilirubinemia